Determination of potassium chlorate residues in 'do' longan fruits - W. Kanaree (2018)
The residues of potassium chlorate (KClO3) in 'Do' longan fruits were determined in CRD, having four treatments (KClO3at 0, 200, 500, and 800 g/tree by soil application) with three replications (one tree/replication). Fruits from KClO3treated and untreated trees were analyzed for chlorate and its derivatives by ion chromatography and atomic absorption spectrophotometry. The results revealed that ClO3-, ClO2-and ClO-residues were not found in the aril of all treated and untreated fruits. Furthermore, K+and Cl-contents in the fruits from KClO3treated and untreated trees were not significantly different (P= 0.05). © ISHS.